Treinamento esfncteriano anal: Estudo transversal em crianças de 3 a 6 anos de idade - de Miranda, José Eduardo G. B. [UNESP] (2011)
Objective: To assess the practice of children's toilet training through interviews with parents and caretakers. Methods: A cross-sectional study of healthy children using a questionnaire applied to parents or caretakers of 100 consecutive children aged 3 to 6 years old. Results: 97% of the children were home-trained by their mothers and 92% of them used their intuition, previous experience with an older child and grandmothers' experience. Bowel and bladder toilet training started simultaneously in 84% of the cases, whereas 41% of the children mastered stool control earlier. Mothers with lower educational level and of social classes C, D and E initiated the training earlier and one of the related reasons was the cost of disposable diapers. Age in initiation or duration of toilet training was similar for boys and girls. Children presented most of the readiness symptoms for toilet training and only a small number of them used a seat reducer or a foot support. There was no increase in constipation prevalence after toilet training and there was no encopresis. Conclusions: Mothers were responsible for bowel toilet training and initiated it with no specialized help. In C-D-E social classes, the cost of diapers was determinant to initiate bowel toilet training.